RELIGIOUS LEADER AND CHARISMATIC LEADERSHIP IN INDONESIA:THE ROLE OF KYAI IN PESANTREN IN JAVA - Ferry Muhammadsyah Siregar (Universitas Gadjah Mada, 2013)
This paper discusses on the role of the kyai in pesantren in Java. It addresses on the roles of religiousleader in pesantren. It applies Max Weber’s concept on religious leadership and charisma. It usesqualitative data for analysis of materials collected from observations and library research. This research????nds that the structures and patterns of leadership and power of Kyai within pesantren are strong inwhich kyai is positioned as the main ????gure. It can be seen on how a kyai build his strategic role as thenon-formal leader in society through intensive communication with the people. The charisma of a kyaialso gains people’s support, to some extents, caused by his moral stability and faith quality. This processat ????rst starts from the nearest group around the pesantren and then spread out to distant places.